2004
DOI: 10.1063/1.1738935
|View full text |Cite
|
Sign up to set email alerts
|

Metal-coated Si springs: Nanoelectromechanical actuators

Abstract: We demonstrated a nanoscale electromechanical actuator operation using an isolated nanoscale spring. The four-turn Si nanosprings were grown using the oblique angle deposition technique with substrate rotation, and were rendered conductive by coating with a 10-nm-thick Co layer using chemical vapor deposition. The electromechanical actuation of a nanospring was performed by passing through a dc current using a conductive atomic force microscope ͑AFM͒ tip. The electromagnetic force leads to spring compression, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 11 publications
0
60
0
Order By: Relevance
“…At low-strain levels, the HN-Fiber behaves as an elastic spring with a spring constant k = 0.12 N/m, with a characteristic upturn in k at higher strain. It is noteworthy that the spring constant obtained earlier is much smaller than those of other nanomaterials having coiled geometry: the superlattice ZnO nanohelices (=4 N/m) [62], metal-coated Si nanocoils (=8.75 N/m) [63], and an array of tightly packed SiO nanocoils (=590 N/m) [64] are by far stiffer than HN-Fibers.…”
Section: Axial Elongationmentioning
confidence: 70%
“…At low-strain levels, the HN-Fiber behaves as an elastic spring with a spring constant k = 0.12 N/m, with a characteristic upturn in k at higher strain. It is noteworthy that the spring constant obtained earlier is much smaller than those of other nanomaterials having coiled geometry: the superlattice ZnO nanohelices (=4 N/m) [62], metal-coated Si nanocoils (=8.75 N/m) [63], and an array of tightly packed SiO nanocoils (=590 N/m) [64] are by far stiffer than HN-Fibers.…”
Section: Axial Elongationmentioning
confidence: 70%
“…To address these challenges, researchers such as Singh et al have demonstrated a nanoscale electromechanical actuator device using an isolated nanoscale spring. 33 The four-turn Si nanosprings were grown using the oblique angle deposition technique with substrate rotation; they were rendered conductive by a 10-nm-thick Co layer applied using chemical vapor deposition. Bargatin et al observed resonances from multiple vibrational modes of individual silicon-carbide-based nanomechanical resonators, covering a broad frequency range from several megahertz to over a gigahertz.…”
Section: Contact Materials For Nanoelectromechanical Devicesmentioning
confidence: 99%
“…Such spiral-like STFs, if flexible enough to withstand defined loads without plastic deformation, could be promising candidates for a variety of applications in the sensing domain, for example, as electromechanical actuators [48]. This motivates the examination of their mechanical behavior, especially in comparison to macroscopic spirals, as will be presented here in terms of the spirals spring constant k. To analyze the elastic deformation of spring-like Si STFs, two samples comprising spirals with different structure parameters have been deposited with GLAD: one 4-turned spiral-like sample of total height h ¼ 2850 AE 50 nm (sample A) and one 13-turned spiral-like sample of total height h ¼ 8400 AE 50 nm (sample B).…”
Section: Spring Constants Of Si Nanospiral Arraysmentioning
confidence: 99%